Plurilingual literary spaces - Tristan Leperlier (Francosphères)
In this article, I define the notion of a plurilingual literary space. While drawing from Pierre Bourdieu’s field theory, I adopt a critical stance towards the highly autonomous, territorialized, and monolingual French case that he studied. Even though language is the material that the writers work with, the legitimate representation of the nation remains the major issue for non-central literary spaces, among which are plurilingual spaces. I elaborate on a typology of plurilingual literary spaces, which are heavily related to the political structure and language policies of the state. Then I concentrate on one of the types, that of plurilingual literary fields, where the language issue is the most significant. I argue that tensions or collaborations between the different linguistic groups depend on the symbolic balance of power between them as well as on official language policies. The most autonomous writers do not always desire to build bridges across language barriers, and they would sometimes rather create identity walls. I distinguish between unitarian policies that lead some linguistically dominated writers to reject collaborations and monolingual policies which lead the autonomous writers to reject the linguistic divisions.